The H- and T-reflex response parameters of long- and short-distance athletes - Ozmerdivenli, R; Bulut, S; Urat, T; Ayar, A (Acad Sciences Czech Republic, Inst Physiology, 2002)
It is well known that the training level of a muscle belongs to the parameters that affect the H-reflex response amplitude. The aim of this study was to investigate the effects of training type on H- and T-reflex response parameters. For this purpose, 20 long-distance athletes (group I, test group), 18 short-distance athletes (group II, test group) and 20 non-trained subjects (group III, control group) were involved in this study in which the H- and T-reflex amplitude and latency values were measured. The H-reflex amplitude and latency values found in groups 1, 11 and III were 3.64 +/- 0.28 mV and 26.88 +/- 1.45 ms, 3.17 +/- 0.26 mV and 26.19 +/- 1.89 ms, and 6.07 +/- 0.34 mV and 26.77 +/- 1.32 ms, respectively. The T-reflex amplitude and latency values of the groups I, II and III were 3.30 +/- 0.18 mV and 32.01 +/- 1.02 ms, 3.11 +/- 0.20 mV and 31.47 +/- 1.16 ms, 4.24 +/- 0.21 mV and 31.47 1.16 ms, respectively. There was no statistically significant difference between the groups with respect to latencies of H- and T-reflexes (p>0.05). In both test groups, the amplitudes of the H-reflex and T-reflex were significantly smaller than the control group (p<0.05). The results of this study suggest that training of muscles affect the H- and T-reflex response parameters.
Keywords: H-reflex; T-reflex; athlete; electromyography; training